2023
DOI: 10.3390/ijms24119727
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Knowledge Regarding WHO High Priority Pathogens—Resistance Mechanisms and Proposed Solutions through Candidates Such as Essential Oils: A Systematic Review

Abstract: Combating antimicrobial resistance (AMR) is among the 10 global health issues identified by the World Health Organization (WHO) in 2021. While AMR is a naturally occurring process, the inappropriate use of antibiotics in different settings and legislative gaps has led to its rapid progression. As a result, AMR has grown into a serious global menace that impacts not only humans but also animals and, ultimately, the entire environment. Thus, effective prophylactic measures, as well as more potent and non-toxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 228 publications
0
9
0
Order By: Relevance
“…It has previously been shown that signals of host adaptation in the genome of Campylobacter transcend those of geographic variation [ 62, 63 ], potentially due to dissemination via global food networks. This host segregating genetic variation is the basis for attributing the source of isolates spread from reservoir hosts to humans [ 24, 64 ]. Consistent with this, it is possible that captive macaques could harbour host specialist lineages similar to those described for chickens, cattle and wild birds [ 20, 65–67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that signals of host adaptation in the genome of Campylobacter transcend those of geographic variation [ 62, 63 ], potentially due to dissemination via global food networks. This host segregating genetic variation is the basis for attributing the source of isolates spread from reservoir hosts to humans [ 24, 64 ]. Consistent with this, it is possible that captive macaques could harbour host specialist lineages similar to those described for chickens, cattle and wild birds [ 20, 65–67 ].…”
Section: Discussionmentioning
confidence: 99%
“… Campylobacter is among the most common causes of bacterial gastroenteritis and rising antimicrobial resistance has led to it being designated a WHO priority pathogen [24]. Increasing genomic surveillance has been informative for identifying infection sources [25–28] and describing the virulence profiles of isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is one of the most dangerous issues that humankind currently faces [1][2][3][4][5]. AMR is propelled by the emergence and spread of multi-drugresistant ESKAPE pathogens consisting of Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp., and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens persist in public places, hospital wards, and emergency units, causing community-and hospital-acquired nosocomial infections, respectively. However, such microorganisms contribute increasingly to higher rates of morbidity and exacerbate treatment challenges, costs, and mortality [1][2][3][4][5]. The COVID-19 pandemic intensified AMR due to the increased use of antimicrobials to treat severely ill patients with comorbidities [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of antibiotics in both human treatments and animal breeding hisolated from poultry meat samples.as caused antimicrobial resistance in Campylobacter to become an increasingly serious problem, and has posed a serious threat to public health over the past two decades ( Luangtongkum et al., 2009 ). In 2017, fluoroquinolone-resistant Campylobacter was listed as one of the six high-priority antimicrobial-resistant pathogens by WHO ( Romanescu et al, 2023 ). In China, bacterial antibiotic resistance monitoring data show that Campylobacter has maintained a high level of resistance to ciprofloxacin (> 90%) in various regions, ( Li et al., 2016 ; Wang et al., 2016 ; Ju et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%